Lymphocyte Count as Predictor of Covid-19 Patients Mortality and Length of Stay in the Covid ICU of Dr Sardjito Hospital - Indra Wijaya, Adi; Jufan, Akhmad Yun; Widodo, Untung (Ahmad Dahlan Medical Journal, 2024)
Covid-19 is an acute infection of the respiratory tract with a variety of clinical manifestations and severity. Lymphocyte count correlates to the severity of Covid-19. This study aims to find the relationship between lymphocyte count, mortality, and length of stay in COVID-19 patients. A retrospective cohort observational studies were conducted using medical records of confirmed COVID-19 patients in RSUP Dr. Sardjito Hospital between 1st January 2021 to 31st December 2021. The lymphocyte count cut-off point as a mortality factor was determined with the ROC curve and Youden’s index. Survival analysis was done using Kaplan Meier to investigate the relation of lymphocyte count to mortality and length of stay. The correlation between lymphocyte count and other factors affecting mortality and length of stay was analyzed with Cox regression. There were 217 subjects who fulfilled the inclusion and exclusion criteria. The cut-off point of lymphocyte count was set at 1.06,103 cells/μL. A total of 121 subjects have a lymphocyte count of <1.06,103 cells/μl. Higher lymphocyte counts (≥1.06,103 cells/μl) showed a reduced risk of mortality (HR 0.570; 95% CI 0.403 – 0.807, p=0.002). The duration of hospitalization was shorter in the group of patients with lymphocyte count <1.06,103 cells/μL OR 0.802, 95% CI 1.032-2.646; p=0.110) with a median of 128.77 hours (12.84 – 983.99 hours), which might be explained by higher mortality (p = 0.000) in the low lymphocyte patients’ group (64.8%). Low lymphocytes <1.06,103 cells/μL in COVID-19 patients is independently and significantly associated with increased risk of mortality and insignificantly associated with shorter length of stay.